Method for producing polarizing film

By using an iodine-containing resin film in the image display device, the problem of the appearance of the polarizing film affecting the display characteristics is solved by using the manufacturing method of contacting the boric acid aqueous solution in the image display device, and an excellent polarizing film is obtained, reducing the Stripes visually recognize and improve display characteristics and power efficiency.

CN119213337APending Publication Date: 2024-12-27NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380039258.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-10
Filing Date
2023-04-07
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In an image display device, the appearance problem of the polarizing film affects the characteristics of the image display. Especially when the polarizing film produces stripes, the stripes will be visually recognized in the image display device, affecting the display effect.

Method used

The manufacturing method of the resin film containing iodine and having a moisture content of 15% by weight is used to contact the boric acid aqueous solution. The monomer transmittance and polarization degree of the resin film are controlled through the steps of air-assisted stretching and water-in-the-water stretching to ensure the polarization film. Excellent appearance and display characteristics.

Benefits of technology

A polarizing film with excellent appearance is achieved, which reduces the visual recognition of stripes in the image display device, improves the display characteristics, and reduces power consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213337A_ABST
    Figure CN119213337A_ABST
Patent Text Reader

Abstract

Provided is a polarizing film which has an excellent appearance and can contribute to improving the display characteristics of an image display device. A method for producing a polarizing film according to an embodiment of the present invention comprises the steps of: bringing a resin film containing iodine and having a moisture content of 15 wt% or less into contact with a first liquid; the first liquid is an aqueous solution of boric acid and iodine, and the temperature of the first liquid is 60 DEG C or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing a polarizing film. Background Art

[0002] In a liquid crystal display device, which is a representative image display device, polarizing films are arranged on both sides of the liquid crystal unit due to its image formation method. In addition, with the popularity of thin displays, displays (OLED) equipped with organic electroluminescent (EL) panels and displays (QLED) using display panels using inorganic light-emitting materials such as quantum dots have also been proposed. These panels have a highly reflective metal layer, which is prone to problems such as external light reflection and background reflection. Therefore, it is known that these problems can be prevented by arranging a circular polarizer with a polarizing film and a λ / 4 plate on the visual recognition side (for example, Patent Document 1 and Patent Document 2).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2002-372622

[0006] Patent Document 2: Japanese Patent No. 3325560 Summary of the invention

[0007] Problems to be solved by the invention

[0008] When a polarizing film is mounted on an image display device as described above, the appearance of the polarizing film may affect the display characteristics of the image display device. For example, when stripes are generated on the polarizing film, the stripes may be visually recognized in the image display device.

[0009] The present invention has been made to solve the above-mentioned problems, and a main object of the present invention is to provide a polarizing film which has an excellent appearance and can contribute to improving the display characteristics of an image display device.

[0010] Means used to solve problems

[0011] 1. The method for manufacturing a polarizing film according to an embodiment of the present invention comprises the following steps: contacting a resin film containing iodine and having a water content of 15 wt % or less with a first liquid; the first liquid is an aqueous solution of boric acid and iodine, and the temperature of the first liquid is above 60° C.

[0012] 2. In the manufacturing method described in 1 above, the single body transmittance of the resin film in contact with the first liquid may be 44% or more.

[0013] 3. In the manufacturing method described in 1 or 2 above, the boric acid concentration of the first liquid can be 3% by weight or more.

[0014] 4. In any one of the manufacturing methods described in 1 to 3 above, the iodine concentration of the first liquid may be 0.002 wt % to 0.01 wt %.

[0015] 5. The manufacturing method according to any one of 1 to 4 above may include the step of bringing the resin film in contact with the first liquid into contact with a second liquid.

[0016] 6. In the manufacturing method described in 5 above, the second liquid may contain water.

[0017] 7. In any one of the manufacturing methods described in 1 to 6 above, a polarizing film having a thickness of 22 μm or less can be obtained.

[0018] Effects of the Invention

[0019] According to the present invention, a polarizing film having excellent appearance can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic cross-sectional view showing a schematic structure of a laminated body according to one embodiment of the present invention.

[0021] Figure 2 This is a schematic diagram showing an example of drying using a heating roller.

[0022] Figure 3 This is a schematic cross-sectional view showing a schematic configuration of a polarizing plate according to one embodiment of the present invention.

[0023] Figure 4 This is a representative diagram of the evaluation of appearance 1 (evaluation results of Comparative Example 5, Example 9, and Example 8).

[0024] Figure 5 This is a representative diagram of the evaluation of appearance 2 (the evaluation results of Comparative Example 5, Example 9, and Example 8). DETAILED DESCRIPTION

[0025] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0026] (Definition of terms and symbols)

[0027] The definitions of terms and symbols in this specification are as follows.

[0028] (1) Refractive index (nx, ny, nz)

[0029] “nx” is the refractive index in the direction where the refractive index in the plane is maximum (ie, the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and “nz” is the refractive index in the thickness direction.

[0030] (2) In-plane phase difference (Re)

[0031] "Re(λ)" is the in-plane phase difference measured at 23°C with light of wavelength λnm. For example, "Re(550)" is the in-plane phase difference measured at 23°C with light of wavelength 550nm. Re(λ) is obtained by the formula: Re(λ) = (nx-ny) × d when the thickness of the layer (film) is set to d (nm).

[0032] (3) Retardation in the thickness direction (Rth)

[0033] "Rth(λ)" is the phase difference in the thickness direction measured at 23°C with light of wavelength λnm. For example, "Rth(550)" is the phase difference in the thickness direction measured at 23°C with light of wavelength 550nm. Rth(λ) is obtained by the formula: Rth(λ) = (nx-nz) × d when the thickness of the layer (film) is set to d (nm).

[0034] (4) Nz coefficient

[0035] The Nz coefficient is obtained by Nz=Rth / Re.

[0036] (5) Angle

[0037] When an angle is mentioned in this specification, the angle includes both clockwise and counterclockwise angles relative to a reference direction. Therefore, for example, "45°" means ±45°.

[0038] The method for producing a polarizing film according to one embodiment of the present invention includes a first step of bringing a resin film containing iodine and having a predetermined moisture content into contact with a first liquid, and may further include a second step of bringing the resin film into contact with a second liquid after the first step.

[0039] A. Method for making resin film

[0040] The resin film can be obtained, for example, by forming a resin layer (typically a polyvinyl alcohol resin layer) on a resin substrate to obtain a laminate or a resin film (typically a polyvinyl alcohol resin film), stretching the laminate or the resin film, dyeing it with a dichroic substance (typically iodine), and then drying it. The following describes the details of the method for producing the resin film using a laminate as an example.

[0041] A-1. Laminated body

[0042] Figure 1Schematic cross-sectional view showing the schematic structure of a laminate according to one embodiment of the present invention. The laminate 1 has a thermoplastic resin substrate (e.g., in a long strip shape) 2 and a polyvinyl alcohol (PVA) resin layer 3. The laminate 1 is preferably produced by forming a PVA resin layer 3 containing a PVA resin and a halide on the thermoplastic resin substrate 2. Specifically, a coating liquid containing a PVA resin and a halide is applied to the thermoplastic resin substrate 2 and dried, thereby forming the PVA resin layer 3.

[0043] The thickness of the thermoplastic resin substrate is preferably 20 μm to 300 μm, more preferably 50 μm to 200 μm. If it is less than 20 μm, it may be difficult to form a PVA-based resin layer. If it is greater than 300 μm, for example, during the water stretching described later, it may take time for the thermoplastic resin substrate to absorb water, and an excessive load may be required for the stretching.

[0044] The water absorption of the thermoplastic resin substrate is preferably 0.2% or more, more preferably 0.3% or more. Such a thermoplastic resin substrate absorbs water, and the water can play the role of a plasticizer to plasticize. As a result, the tensile stress can be greatly reduced, and it can be stretched at a high ratio. On the other hand, the water absorption of the thermoplastic resin substrate is preferably 3.0% or less, more preferably 1.0% or less. Such a water absorption can prevent undesirable situations such as a significant reduction in the dimensional stability of the thermoplastic resin substrate during manufacturing and deterioration in the quality of the resulting polarizing film. It can also prevent the thermoplastic resin substrate from breaking or the PVA-based resin layer from peeling off during stretching in water. The water absorption of the thermoplastic resin substrate can be adjusted by, for example, introducing a modifying group into the constituent material. In addition, the water absorption is a value obtained in accordance with JIS K 7209.

[0045] The glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 120°C or less. By using such a thermoplastic resin substrate, the crystallization of the PVA-based resin layer can be suppressed, and the stretchability of the laminate can be fully ensured. In addition, considering the use of water to plasticize the thermoplastic resin substrate and well stretching in water, Tg is more preferably 100°C or less, and further preferably 90°C or less. On the other hand, the Tg of the thermoplastic resin substrate is preferably 60°C or more. By such a Tg, the thermoplastic resin substrate can be prevented from deforming (such as unevenness or sagging, wrinkling, etc.) when applying and drying the above-mentioned coating solution, thereby making the laminate well. In addition, the above-mentioned resin layer can be stretched well at a suitable temperature (such as about 60°C). The Tg of the thermoplastic resin substrate can be adjusted by, for example, heating a crystallizing material using a modified group introduced into the constituent material. In addition, the glass transition temperature (Tg) is a value obtained in accordance with JIS K 7121.

[0046] As the constituent material of the thermoplastic resin substrate, any appropriate thermoplastic resin can be used. As the thermoplastic resin, for example, ester resins such as polyethylene terephthalate resins, cycloolefin resins such as norbornene resins, olefin resins such as polypropylene, polyamide resins, polycarbonate resins, and copolymer resins thereof can be cited. Among them, norbornene resins and amorphous polyethylene terephthalate resins are preferred.

[0047] In one embodiment, it is preferred to use an amorphous (uncrystallized) polyethylene terephthalate resin. Among them, it is particularly preferred to use an amorphous (difficult to crystallize) polyethylene terephthalate resin. As specific examples of amorphous polyethylene terephthalate resins, copolymers further comprising isophthalic acid and / or cyclohexanedicarboxylic acid as dicarboxylic acids, or copolymers further comprising cyclohexanedimethanol or diethylene glycol as glycols can be cited.

[0048] In another embodiment, a polyethylene terephthalate resin having an isophthalic acid unit is preferably used. The reason is that the stretchability is extremely excellent and crystallization during stretching can be suppressed. This is believed to be because the introduction of the isophthalic acid unit gives the main chain a large bend. The polyethylene terephthalate resin has terephthalic acid units and ethylene glycol units. The content ratio of the isophthalic acid unit relative to the total of all repeating units is preferably 0.1 mol% or more, more preferably 1.0 mol% or more. The reason is that a thermoplastic resin substrate with extremely excellent stretchability can be obtained. On the other hand, the content ratio of the isophthalic acid unit relative to the total of all repeating units is preferably 20 mol% or less, more preferably 10 mol% or less. The reason is that the degree of crystallization can be well increased in the drying described later.

[0049] The thermoplastic resin substrate may also be stretched in advance (for example, before forming the PVA-based resin layer). In one embodiment, the thermoplastic resin substrate is stretched in the transverse direction of the long strip. The transverse direction is preferably a direction orthogonal to the stretching direction of the laminate described later. In addition, the so-called "orthogonal" in this specification also includes substantially orthogonal situations. Here, the so-called "substantially orthogonal" includes the case of 90°±5.0°, preferably 90°±3.0°, and more preferably 90°±1.0°. Relative to the glass transition temperature (Tg) of the thermoplastic resin substrate, the stretching temperature of the thermoplastic resin substrate is preferably Tg-10°C to Tg+50°C. The stretching ratio of the thermoplastic resin substrate is preferably 1.5 times to 3.0 times. The stretching method of the thermoplastic resin substrate can adopt any appropriate method. Specifically, it can be fixed-end stretching or free-end stretching. The stretching method can be dry or wet. Stretching can be carried out in one stage or in multiple stages. When the stretching is performed in multiple stages, the above-mentioned stretching ratio is the product of the stretching ratios in each stage.

[0050] The coating liquid is typically a solution obtained by dissolving a PVA resin and a halide in a solvent. Examples of the solvent include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyols such as trimethylolpropane, amines such as ethylenediamine and diethylenetriamine. They can be used alone or in combination of two or more. Water is preferred among them. The content of the PVA resin in the coating liquid is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. According to the range, a uniform coating film that is closely attached to a thermoplastic resin substrate can be formed. The halide content in the coating liquid is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA resin.

[0051] As the above-mentioned PVA-based resin, for example, polyvinyl alcohol and ethylene-vinyl alcohol copolymer can be cited. Polyvinyl alcohol can be obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer can be obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of PVA-based resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. By using a PVA-based resin with the above-mentioned saponification degree, a polarizing film with excellent durability can be obtained. When the saponification degree is too high, gelation may occur. In addition, the saponification degree can be obtained according to JIS K 6726-1994.

[0052] The average degree of polymerization of the PVA-based resin is usually 1,000 to 10,000, preferably 1,200 to 4,500, and more preferably 1,500 to 4,300. The average degree of polymerization can be determined in accordance with JIS K 6726-1994.

[0053] As the above-mentioned halide, any appropriate halide can be used. For example, iodides such as potassium iodide, sodium iodide, and lithium iodide, and chlorides such as sodium chloride can be listed. Potassium iodide is preferred among them. By using a halide, a polarizing film with excellent optical properties can be obtained. Specifically, it can promote the crystallization of the PVA-based resin after the air-assisted stretching described later, and in the subsequent wet treatment (such as the dyeing and underwater stretching described later), the orientation disorder and orientation reduction of the polyvinyl alcohol molecules can be suppressed, and a polarizing film with excellent optical properties can be obtained.

[0054] In the preparation of the coating liquid, the halide is preferably added in an amount of 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, relative to 100 parts by weight of the PVA resin. Specifically, the content of the halide in the resulting PVA resin layer is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, relative to 100 parts by weight of the PVA resin. If the amount of the halide is large relative to the amount of the PVA resin, the halide may ooze out, and the resulting polarizing film may become turbid.

[0055] The coating liquid may also be mixed with additives. Examples of additives include plasticizers and surfactants. Examples of plasticizers include polyols such as ethylene glycol and glycerol. Examples of surfactants include nonionic surfactants. These are used, for example, to improve the uniformity, dyeability, and stretchability of the resulting PVA-based resin layer.

[0056] Examples of the coating method of the coating liquid include roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, and knife coating (comma coating). The coating and drying temperature of the coating liquid is preferably 50° C. or higher.

[0057] The thickness of the PVA-based resin layer is preferably 3 μm to 40 μm, more preferably 3 μm to 20 μm.

[0058] Before forming the PVA-based resin layer, the thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment), or an easy-adhesion layer may be formed on the thermoplastic resin substrate. By performing the above treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved.

[0059] A-2. Stretching

[0060] The above-mentioned stretching is preferably carried out by stretching in water after the above-mentioned laminate is dry-stretched (auxiliary stretching in the air). Through auxiliary stretching, the crystallization of the above-mentioned thermoplastic resin substrate can be suppressed while stretching, and the problem of reduced stretchability caused by excessive crystallization of the thermoplastic resin substrate in boric acid water stretching can be solved, and the laminate can be stretched at a higher ratio. In addition, when using a thermoplastic resin substrate, the above-mentioned coating temperature can be set to a lower level, so the crystallization of the PVA-based resin may be relatively low and sufficient optical properties cannot be obtained. In this regard, by introducing auxiliary stretching, the crystallinity of the PVA-based resin can be improved even when using a thermoplastic resin. In addition, by improving the orientation of the PVA-based resin in advance, problems such as reduced orientation or dissolution of the PVA-based resin during subsequent wet treatment can be prevented. In this way, a polarizing film with excellent optical properties can be obtained.

[0061] The method of aerial auxiliary stretching may be fixed-end stretching (for example, a method of stretching using a tenter stretching machine) or free-end stretching (for example, a method of passing the laminate through rollers with different circumferential speeds for single-screw stretching). Free-end stretching is preferably used. For example, heating roller stretching is used to stretch the laminate by conveying the laminate along its length while using the circumferential speed difference between heating rollers. In one embodiment, aerial auxiliary stretching includes a regional stretching process and a heating roller stretching process in a hot space (region). The order of the regional stretching process and the heating roller stretching process is not limited, but for example, the regional stretching process and the heating roller stretching process are performed in sequence. In another embodiment, the end of the film is held in a tenter stretching machine, and the distance between the tenters is expanded along the flow direction for stretching (the increase in the distance between the tenters becomes the stretching ratio). At this time, the distance of the tenters in the width direction (vertical to the flow direction) is preferably set to be close to the stretching ratio relative to the flow direction to utilize free-end stretching. In the case of free-end stretching, the shrinkage rate in the width direction is expressed by the formula: Shrinkage rate in the width direction = (1 / stretching ratio) 1 / 2 to calculate.

[0062] The stretching ratio of the aerial auxiliary stretching is preferably 2.0 to 3.5 times. The aerial auxiliary stretching can be performed in one stage or in multiple stages. When performed in multiple stages, the stretching ratio is the product of the stretching ratios of each stage. The stretching direction in the aerial auxiliary stretching is preferably substantially the same as the stretching direction of the underwater stretching described later.

[0063] The stretching temperature of the aerial auxiliary stretching is set to any appropriate value, for example, according to the thermoplastic resin substrate used, the stretching method, etc. The stretching temperature is preferably above the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably above Tg+10°C, and further preferably above Tg+15°C. On the other hand, the upper limit of the stretching temperature is preferably 170°C. By stretching at such a temperature, the rapid progress of crystallization of the PVA-based resin can be suppressed, and the adverse conditions caused by the crystallization (for example, the orientation of the PVA-based resin layer is hindered due to stretching) can be suppressed.

[0064] The above-mentioned underwater stretching is typically performed by immersing the laminate in a stretching bath. Through underwater stretching, the laminate can be stretched at a temperature lower than the glass transition temperature (typically about 80° C.) of the above-mentioned thermoplastic resin substrate or the PVA-based resin layer, and the crystallization of the PVA-based resin layer can be suppressed while stretching at a high ratio. As a result, a polarizing film with excellent optical properties can be obtained.

[0065] The method of underwater stretching may be fixed end stretching or free end stretching (for example, a method of passing the laminate through rollers with different peripheral speeds for single screw stretching). Free end stretching is preferably used. The stretching of the laminate may be carried out in one stage or in multiple stages. When it is carried out in multiple stages, the stretching ratio of the laminate described below is the product of the stretching ratios of each stage.

[0066] The underwater stretching is preferably performed by immersing the laminate in an aqueous solution of boric acid (boric acid underwater stretching). By using an aqueous solution of boric acid as a stretching bath, the PVA-based resin layer can be given rigidity and water resistance that can withstand the tension applied during stretching. Specifically, boric acid generates tetrahydroxyborate anions in an aqueous solution and can be cross-linked with the PVA-based resin through hydrogen bonds. As a result, the PVA-based resin layer can be given rigidity and water resistance and stretched well, and a polarizing film with excellent optical properties can be obtained.

[0067] The above-mentioned boric acid aqueous solution is preferably obtained by dissolving boric acid and / or a borate in a solvent, i.e., water. The boric acid concentration is preferably 1 to 10 parts by weight, more preferably 2.5 to 6 parts by weight, and further preferably 3 to 5 parts by weight relative to 100 parts by weight of water. By setting the boric acid concentration to be 1 part by weight or more, the dissolution of the PVA-based resin layer can be effectively suppressed, and a polarizing film with higher characteristics can be manufactured. In addition, in addition to boric acid or a borate, an aqueous solution obtained by dissolving a boron compound such as borax, glyoxal, glutaraldehyde, etc. in a solvent can also be used.

[0068] It is preferred to add an iodide to the stretching bath (boric acid aqueous solution). By adding an iodide, the dissolution of iodine adsorbed on the PVA-based resin layer can be suppressed. Examples of the iodide include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. The concentration of the iodide is preferably 0.05 to 15 parts by weight, more preferably 0.5 to 8 parts by weight, relative to 100 parts by weight of water.

[0069] The stretching temperature (liquid temperature of the stretching bath) is preferably above 40°C, more preferably above 60°C. At such a temperature, the dissolution of the PVA-based resin layer can be suppressed while stretching at a high ratio. Specifically, as described above, in relation to the formation of the PVA-based resin layer, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably above 60°C. At this time, if the stretching temperature is lower than 40°C, even if the thermoplastic resin substrate is plasticized with water, it may not be stretched well. On the other hand, the stretching temperature is, for example, below 70°C, preferably below 67°C, and more preferably below 65°C. The higher the stretching temperature, the higher the solubility of the PVA-based resin layer, and it may not be possible to obtain excellent optical properties. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.

[0070] The stretching ratio by underwater stretching is preferably 1.5 times or more, more preferably 3.0 times or more. The total stretching ratio of the laminate (the stretching ratio of the combined air auxiliary stretching and underwater stretching) is preferably 5.0 times or more, more preferably 5.5 times or more, and further preferably 6.0 times or more relative to the original length of the laminate. By achieving such a high stretching ratio, a polarizing film with excellent optical properties can be manufactured. Such a high stretching ratio can be achieved by adopting an underwater stretching method (boric acid underwater stretching).

[0071] A-3. Dyeing

[0072] The dyeing is typically performed by adsorbing iodine on the PVA resin layer. As the method for adsorbing iodine, for example, the method of immersing the PVA resin layer (laminated body) in a dyeing solution containing iodine, the method of applying the dyeing solution on the PVA resin layer, and the method of spraying the dyeing solution on the PVA resin layer can be cited. Preferably, the method of immersing the laminate in a dyeing solution (dyeing bath) is used. This is because iodine can be adsorbed well.

[0073] The dyeing solution is preferably an iodine aqueous solution. The amount of iodine added is preferably 0.05 to 0.5 parts by weight relative to 100 parts by weight of water. In order to increase the solubility of iodine in water, it is preferred to add an iodide to the iodine aqueous solution. Specific examples of iodide are as described above. Potassium iodide can preferably be used. The amount of iodide added is preferably 0.1 to 10 parts by weight relative to 100 parts by weight of water, and more preferably 0.3 to 5 parts by weight. In order to suppress the dissolution of the PVA-based resin, the liquid temperature of the dyeing solution during dyeing is preferably 20°C to 50°C. When the PVA-based resin layer is immersed in the dyeing solution, in order to ensure the transmittance of the PVA-based resin layer, the immersion time is preferably 5 seconds to 5 minutes, and more preferably 30 seconds to 90 seconds.

[0074] The dyeing conditions (concentration, liquid temperature, immersion time) can be set, for example, so that the monomer transmittance of the obtained resin film is 42% or more and the polarization degree is 85% or more. Regarding such dyeing conditions, for example, in the iodine aqueous solution as the dyeing liquid, the content ratio of iodine and potassium iodide is preferably set to 1:5 to 1:20, and more preferably 1:5 to 1:10.

[0075] When the laminate is immersed in a treatment bath containing boric acid (for example, the insolubility treatment described below) and then dyed, boric acid will be mixed into the dyeing bath to change the boric acid concentration of the dyeing bath, and there is a situation where the dyeing property becomes unstable. In order to suppress such instability of dyeing property, the boric acid concentration of the dyeing bath is preferably adjusted to less than 4 parts by weight, more preferably adjusted to less than 2 parts by weight relative to 100 parts by weight of water. On the other hand, the boric acid concentration of the dyeing bath is preferably 0.1 parts by weight or more, more preferably 0.2 parts by weight or more, and further preferably 0.5 parts by weight or more relative to 100 parts by weight of water. In one embodiment, dyeing is performed using a dyeing bath pre-containing boric acid. According to such a form, the proportion of the change in boric acid concentration when boric acid is mixed into the dyeing bath can be reduced. The amount of boric acid pre-mixed in the dyeing bath (not the content of boric acid from the above-mentioned treatment bath) is preferably 0.1 to 2 parts by weight, more preferably 0.5 to 1.5 parts by weight relative to 100 parts by weight of water.

[0076] A-4. Other treatments

[0077] If necessary, an insolubility treatment is performed after the above-mentioned auxiliary stretching in the air and before stretching and dyeing in water. The insolubility treatment is typically performed by immersing the PVA-based resin layer in an aqueous solution of boric acid. By performing the insolubility treatment, the PVA-based resin layer can be given water resistance to prevent the orientation of the PVA from being reduced when immersed in water. The concentration of the aqueous solution of boric acid in the insolubility treatment is preferably 1 to 4 parts by weight relative to 100 parts by weight of water. The temperature of the insolubility treatment (liquid temperature of the aqueous solution of boric acid) is preferably 20°C to 50°C.

[0078] If necessary, a cross-linking treatment is performed after dyeing and before stretching in water. The cross-linking treatment is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. By performing the cross-linking treatment, water resistance can be imparted to the PVA-based resin layer, thereby preventing the orientation of the PVA from being reduced during subsequent stretching in water. The concentration of the aqueous boric acid solution in the cross-linking treatment is preferably 1 to 5 parts by weight relative to 100 parts by weight of water. It is preferred to add an iodide to the aqueous boric acid solution. By adding an iodide, the dissolution of iodine adsorbed to the PVA-based resin layer can be suppressed. Specific examples of iodides are as described above. The amount of iodide added is preferably 1 to 5 parts by weight relative to 100 parts by weight of water. The temperature of the cross-linking treatment (liquid temperature of the aqueous boric acid solution) is preferably 20°C to 50°C.

[0079] It is preferred to perform washing after stretching in water and before drying described below. Washing is typically performed by immersing the PVA-based resin layer in an aqueous potassium iodide solution.

[0080] A-5. Drying

[0081] The above-mentioned drying can be carried out in any appropriate manner and under any appropriate conditions. Specifically, it can be carried out by heating the entire area (regional heating method) or by heating the conveying roller (heating roller method). The heating roller method is preferably adopted, and the two are more preferably adopted. By using a heating roller, the heating curling of the laminate can be effectively suppressed, and a polarizing film of excellent quality can be manufactured. Specifically, by drying the laminate along the heating roller, the crystallization of the above-mentioned thermoplastic resin substrate can be effectively promoted to increase the crystallinity, and even at a relatively low drying temperature, the crystallinity of the thermoplastic resin substrate can still be well increased. As a result, the rigidity of the thermoplastic resin substrate will increase and become a state that can withstand the shrinkage of the PVA-based resin layer caused by drying, thereby suppressing curling. In addition, by using a heating roller, the laminate can be maintained in a flat state while being dried, so not only curling can be suppressed, but also wrinkling can be suppressed.

[0082] By drying, the laminate can be shrunk in the width direction and the optical properties can be improved. The reason is that the orientation of PVA and PVA / iodine complex can be effectively improved. The shrinkage rate in the width direction caused by drying the laminate is preferably 1% to 10%, more preferably 2% to 8%, and further preferably 4% to 6%. By using a heated roller, the laminate can be continuously shrunk in the width direction while being transported, and high productivity can be achieved.

[0083] Figure 2 This is a schematic diagram showing an example of drying using a heating roller. In the example shown in the figure, the laminate 200 is dried while being conveyed by conveying rollers R1 to R6 and guide rollers G1 to G4 that have been heated to a predetermined temperature. In the example shown in the figure, the conveying rollers R1 to R6 are arranged so as to alternately and continuously heat the surface of the PVA resin layer and the surface of the thermoplastic resin substrate, but, for example, the conveying rollers R1 to R6 may be arranged so as to continuously heat only one side of the laminate 200 (for example, the surface of the thermoplastic resin substrate).

[0084] The drying conditions can be controlled by adjusting the heating temperature of the conveying roller (the temperature of the heating roller), the number of heating rollers, the contact time with the heating roller, etc. The temperature of the heating roller is preferably 60°C to 120°C, more preferably 65°C to 100°C, and further preferably 70°C to 80°C. According to such a temperature, the crystallinity of the thermoplastic resin can be increased to suppress curling, and the laminate can be given extremely excellent durability. In addition, the temperature of the heating roller can be measured using a contact thermometer. In the example shown in the figure, 6 conveying rollers are provided, but there is no particular limitation as long as there are multiple conveying rollers. Conveying rollers are usually provided in 2 to 40 numbers, preferably 4 to 30 numbers. The contact time (total contact time) between the laminate and the heating roller is preferably 1 second to 300 seconds, more preferably 1 to 20 seconds, and further preferably 1 to 10 seconds.

[0085] The heating roller can be set in a heating furnace (such as an oven) or in a conventional manufacturing production line (under room temperature). It is preferably set in a heating furnace equipped with an air supply mechanism. By using drying using a heating roller and hot air drying together, the rapid temperature change between the heating rollers can be suppressed, and the shrinkage in the width direction can be easily controlled. The temperature of hot air drying is preferably 30°C to 100°C. In addition, the hot air drying time is preferably 1 second to 300 seconds. The wind speed of the hot air is preferably about 10m / second to 30m / second. In addition, the wind speed is the wind speed in the heating furnace and can be measured using a mini fan-type digital anemometer.

[0086] A-6. Resin film

[0087] The moisture content of the resin film provided for the first step described later is, for example, 15 wt % or less, preferably 12 wt % or less, more preferably 9 wt % or less, and further preferably 6 wt % or less. On the other hand, the moisture content of the resin film is, for example, 3 wt % or more. The resin film after the above drying can satisfy the above moisture content.

[0088] The resin film provided for the first step described later preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single body transmittance (Ts) of the resin film is, for example, 42% or more, preferably 44% or more. The higher the transmittance becomes, the easier it is to visually recognize the stripes. On the other hand, the single body transmittance (Ts) of the resin film is, for example, 49% or less.

[0089] The polarization degree (P) of the resin film subjected to the first step described below is, for example, 85% or more, preferably 90% or more, more preferably 95% or more, and further preferably 98% or more. On the other hand, the polarization degree of the polarizing film of the resin film is, for example, 99.996% or less.

[0090] The single transmittance is typically measured using an ultraviolet visible spectrophotometer and corrected for visibility as a Y value. The polarization degree is typically obtained by the following formula based on the parallel transmittance Tp and the orthogonal transmittance Tc measured using an ultraviolet visible spectrophotometer and corrected for visibility.

[0091] Polarization degree (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0092] The orientation of the resin film (orientation of PVA) to be used in the first step described below is, for example, 0.20 or more, preferably 0.25 or more, and more preferably 0.30 or more. On the other hand, the orientation of the resin film (orientation of PVA) is, for example, 0.40 or less.

[0093] The above-mentioned orientation can be obtained, for example, by the following method: using a Fourier transform infrared spectrometer (e.g., the model "Frontier FT-IR" manufactured by PerkinElmer) to measure the spectrum of the resin film (polarizing film) by the ATR method, and calculating the orientation of PVA from the obtained spectrum results. Specifically, for the resin film (polarizing film), the spectrum is measured for polarized light incident at 0° and 90°, and the 2940cm-1 derived from -OH is calculated. -1 and 3300cm -1 The peak intensity ratio a(I 2940 / I 3330 Then, calculate the ratio b of the intensity ratio a (at an incident angle of 0°) to the intensity ratio a (at an incident angle of 90°). 0° / a 90° ) as the two-color ratio, and c = (1-b) / [(2b + 1) × (-2)] as an index of orientation. Here, the higher the value of c, the higher the orientation of PVA.

[0094] The thickness of the resin film used in the first step described below is, for example, 22 μm or less, 16 μm or less, 12 μm or less, 8 μm or less, or 6 μm or less. On the other hand, the thickness of the resin film is preferably 1 μm or more, more preferably 2 μm or more.

[0095] B-1. First step

[0096] As described above, in the first step, the resin film is contacted with the first liquid. The resin film is preferably immersed in the first liquid. When the resin film is immersed in the first liquid, one side of the resin film may also be supported (protected) by any appropriate supporting substrate. In one embodiment, the supporting substrate uses the above-mentioned resin substrate. Specifically, the resin film is immersed in the first liquid without peeling the resin substrate from the resin film (in the state of the above-mentioned laminate). In another embodiment, the supporting substrate uses the protective layer described later. For example, after the protective layer is laminated on the surface of the resin film of the above-mentioned laminate, the resin substrate is peeled off from the resin film to produce a laminate of the protective layer and the resin film, and the laminate is immersed in the first liquid. When immersed in the first liquid, the resin film may be in the form of a long strip or a single sheet.

[0097] By contacting with the first liquid, a polarizing film with excellent appearance can be obtained. Specifically, by contacting with the first liquid, the orientation of the resin film (the orientation of PVA) is reduced, and the components originally contained in the resin film (such as borate ions and iodine ions) will enter and exit the resin film, which can make the streaks generated in the resin film disappear. The difference in orientation (the orientation of PVA) of the resin film before and after contact with the first liquid is, for example, 0.05 to 0.2. The orientation (the orientation of PVA) of the resin film after contacting the first liquid is, for example, 0.10 to 0.30.

[0098] By contacting with the first liquid, the monomer transmittance (Ts) of the resin film increases. The difference in monomer transmittance (Ts) of the resin film before and after contacting the first liquid is preferably 1.5% or more, more preferably 3% or more, 5% or more, or 7% or more. On the other hand, the difference in monomer transmittance (Ts) of the resin film before and after contacting the first liquid is preferably 10% or less. The monomer transmittance (Ts) of the resin film after contacting the first liquid is, for example, 45% or more, preferably 47% or more. On the other hand, the monomer transmittance (Ts) of the resin film after contacting the first liquid is preferably 55% or less.

[0099] The polarization degree (P) of the resin film decreases by contacting the first liquid. The difference in polarization degree (P) of the resin film before and after contacting the first liquid is, for example, 10% to 20%. The polarization degree (P) of the resin film after contacting the first liquid is, for example, 65% to 97%.

[0100] The temperature of the first liquid when in contact with the resin film is, for example, 60°C or higher, 65°C or higher, 70°C or higher, or 75°C or higher. By using the first liquid at the above temperature, for example, the orientation of the resin film (orientation of PVA) can be reduced. On the other hand, the temperature of the first liquid is, for example, 90°C or lower, preferably 85°C or lower.

[0101] The immersion time (contact time) in the first liquid can be set, for example, according to the temperature of the first liquid, the thickness of the resin film, the concentration of the components contained in the first liquid, etc. The immersion time in the first liquid is, for example, 1 to 60 minutes, preferably 2 to 30 minutes.

[0102] As the first liquid, an aqueous boric acid solution is preferably used. By using an aqueous boric acid solution, the orientation of the resin film (the orientation of PVA) can be well reduced. For example, even if the temperature of the first liquid is increased (for example, set to above 60°C), the orientation of the PVA can be reduced (the PVA chain can be relaxed) without dissolving the resin film in the first liquid, and the PVA can be re-crosslinked and homogenized by the entry and exit of boric acid ions. The concentration of the aqueous boric acid solution is preferably 3% by weight or more, more preferably 4% by weight or more. On the other hand, from the viewpoint of the solubility of boric acid, the concentration of the aqueous boric acid solution is, for example, 8% by weight or less.

[0103] The first liquid preferably contains iodine. By containing iodine, the inflow and outflow of components originally contained in the resin film can be promoted. The iodine concentration in the first liquid is preferably 0.002 weight % or more. On the other hand, the iodine concentration in the first liquid is preferably 0.01 weight % or less, more preferably 0.005 weight % or less. According to the concentration, it is also possible to prevent the resin film from being preferentially dyed by the inflow and outflow of components originally contained in the resin film.

[0104] From the viewpoint of improving the solubility of iodine, the first liquid may contain an iodide such as potassium iodide, for example. The concentration of the iodide is, for example, 0.007% by weight to 1% by weight.

[0105] B-2. Second process

[0106] As described above, in the second step, the resin film is brought into contact with the second liquid. Typically, the resin film is immersed in the second liquid. When the resin film is immersed in the second liquid in the same manner as in the first step, one side of the resin film is preferably supported (protected) by any appropriate supporting substrate. The details are as described above. By contacting with the second liquid, the resin film can be cleaned (for example, by boric acid cleaning). In addition, by contacting with the second liquid, the hue of the resulting polarizing film can be adjusted.

[0107] By contacting with the second liquid, the monomer transmittance (Ts) of the resin film is reduced. In one embodiment, the processing conditions using the second liquid are adjusted according to the desired optical properties (e.g., monomer transmittance, polarization degree) of the obtained polarizing film. The difference in monomer transmittance (Ts) of the resin film before and after contact with the second liquid is, for example, 0.1% to 10%. In addition, the monomer transmittance (Ts) of the resin film after contacting the second liquid is equivalent to the monomer transmittance (Ts) of the polarizing film described later.

[0108] The polarization degree (P) of the resin film increases by contacting with the second liquid. The difference in the polarization degree (P) of the resin film before and after contacting the second liquid is, for example, 0.1% to 20%. In addition, the polarization degree (P) of the resin film after contacting the second liquid is equivalent to the polarization degree (P) of the polarizing film described later.

[0109] Contact with the second liquid increases the orientation of the resin film (orientation of PVA). The difference in orientation of the resin film before and after contact with the second liquid (orientation of PVA) is, for example, 0.01 to 0.10. The orientation of the resin film after contact with the second liquid (orientation of PVA) is, for example, 0.15 to 0.35.

[0110] The temperature when the second liquid contacts the resin film is typically set to room temperature, for example, 15° C. to 40° C. The immersion time (contact time) in the second liquid is, for example, 1 second to 1 minute.

[0111] The second liquid typically contains an aqueous solvent (preferably water). The second liquid may also contain an iodide such as potassium iodide. By containing an iodide, the obtained polarizing film can be suppressed from being bluish. The concentration of the iodide in the iodide second liquid is, for example, 0 wt% to 6 wt%.

[0112] B-3. ​​Other processes

[0113] The resin film (polarizing film) after the second step may be dried at a drying temperature of, for example, 30° C. to 60° C. and for a drying time of, for example, 15 seconds to 3 minutes.

[0114] C. Polarizing film

[0115] The polarizing film obtained by the manufacturing method of the embodiment of the present invention can show absorption dichroism at any wavelength of 380nm to 780nm. The single transmittance (Ts) of the polarizing film is preferably 42% or more, 44% or more, or 46% or more. According to the transmittance, it can help to reduce the power consumption of the mounted image display device. According to the manufacturing method of the embodiment of the present invention, a polarizing film having both high transmittance and excellent appearance can be obtained. On the other hand, the single transmittance (Ts) of the polarizing film is, for example, less than 55%, less than 50%, or less than 48%.

[0116] The polarization degree (P) of the polarizing film is, for example, 70% or more, preferably 75% or more, and more preferably 85% or more. On the other hand, the polarization degree of the polarizing film is, for example, 98% or less.

[0117] The orientation of the polarizing film (orientation of PVA) is preferably 0.20 or more, and more preferably 0.25 or more. On the other hand, the orientation of the resin film (orientation of PVA) is, for example, 0.35 or less.

[0118] The thickness of the polarizing film is, for example, 22 μm or less, 16 μm or less, 12 μm or less, 8 μm or less, or 6 μm or less. On the other hand, the thickness of the polarizing film is preferably 1 μm or more, more preferably 2 μm or more.

[0119] D. Polarizer

[0120] A polarizing plate according to one embodiment of the present invention includes the polarizing film described above, and a protective layer or a retardation layer disposed on at least one side of the polarizing film.

[0121] Figure 3 It is a schematic cross-sectional view showing the general structure of a polarizing plate according to one embodiment of the present invention. The polarizing plate (polarizing plate with a phase difference layer) 100 comprises: a polarizing film 10 having a first principal surface 10a and a second principal surface 10b facing each other; a protective layer 20, which is arranged on the first principal surface 10a side (e.g., the visual recognition side) of the polarizing film 10; and a phase difference layer 30 and an adhesive layer 40, which are arranged on the second principal surface 10b side of the polarizing film 10. The phase difference layer 30 may be a single layer or may have a laminated structure having two or more layers laminated. In addition, a second protective layer may be arranged between the polarizing film 10 and the phase difference layer 30.

[0122] Although not shown, the polarizer may also further have other functional layers. The type, characteristics, quantity, combination, configuration, etc. of the functional layers that the polarizer may have can be appropriately set according to the purpose. For example, the polarizer may also further have a conductive layer or an isotropic substrate with a conductive layer. A polarizer having a conductive layer or an isotropic substrate with a conductive layer (a polarizer with a phase difference layer) is used, for example, in a so-called internal touch panel input display device in which a touch sensor is assembled inside an image display panel. As another example, the polarizer may also further have other phase difference layers. The optical properties (such as refractive index characteristics, in-plane phase difference, Nz coefficient, photoelastic coefficient), thickness, configuration, etc. of other phase difference layers can be appropriately set according to the purpose. As a specific example, other phase difference layers (representatively, layers that impart (elliptical) circular polarization function, layers that impart ultra-high phase difference) to improve the visual recognition when visually recognized through polarized sunglasses may also be provided on the visual recognition side of the polarizing film 10. By having the layer, even when the display screen is visually recognized through polarized lenses such as polarized sunglasses, excellent visual recognition can still be achieved. Therefore, the obtained polarizing plate (polarizing plate with a retardation layer) can also be suitably used in an image display device that can be used outdoors.

[0123] Each component constituting the polarizer can be stacked via any appropriate adhesive layer (not shown). Specific examples of the adhesive layer include an adhesive layer and an adhesive layer. Specifically, the phase difference layer 30 can be bonded to the polarizing film 10 or the second protective layer via an adhesive layer (preferably using an active energy ray-curing adhesive), or can be bonded to the polarizing film 10 or the second protective layer via an adhesive layer. When the phase difference layer 30 has a laminated structure of more than two layers, each phase difference layer can be bonded, for example, via an adhesive layer (preferably using an active energy ray-curing adhesive).

[0124] Although not shown, in actual use, a release liner is attached to the surface of the adhesive layer 40. The release liner may be temporarily attached until the polarizing plate is used. By using a release liner, for example, the adhesive layer 40 can be protected and a roll of the polarizing plate can be formed.

[0125] The polarizer may be in the form of a strip or a single sheet. In this specification, the term "strip" refers to an elongated shape that is sufficiently long relative to its width, for example, an elongated shape that is 10 times or more, preferably 20 times or more, longer relative to its width. The elongated polarizer may be wound into a roll.

[0126] D-1. Protective layer

[0127] The above protective layer can be formed of any suitable thin film that can be used as a protective layer for a polarizing film. Specific examples of the material that is the main component of the thin film include: cellulose-based resins such as triacetyl cellulose (TAC), or transparent resins such as polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene-based, polyolefin-based, (meth)acrylic-based, and acetate-based.

[0128] The above polarizing plate is typically disposed on the visual recognition side of the image display device. Therefore, the protective layer 20 can also be subjected to surface treatments such as hard coat (HC) treatment, antireflection treatment, antiadhesion treatment, antiglare treatment, etc. as needed.

[0129] The thickness of the protective layer is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and still more preferably 10 μm to 30 μm. In addition, when the above surface treatment is performed, the thickness of the protective layer is the thickness including the thickness of the surface treatment layer.

[0130] In one embodiment, the second protective layer disposed between the polarizing film 10 and the retardation layer 30 is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation in the thickness direction Rth(550) is -10 nm to +10 nm.

[0131] In one embodiment, the above resin substrate can be directly used as the protective layer of the polarizing film. According to this form, the manufacturing process can be reduced.

[0132] D-2. Retardation layer

[0133] The retardation layer 30 can be a single layer as described above, or can have a laminated structure (for example, a two-layer structure).

[0134] The retardation layer 30 can have any suitable optical characteristics according to the use and the like. In one embodiment, the retardation layer 30 includes a first retardation layer that can function as a λ / 4 plate. The first retardation layer typically exhibits a refractive index characteristic of nx > ny = nz. The in-plane retardation Re(550) of the retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and still more preferably 120 nm to 160 nm. In addition, here "ny = nz" includes not only the case where ny and nz are exactly equal, but also the case where they are substantially equal. Therefore, within the range that does not impair the effects of the present invention, there may be cases where ny > nz or ny < nz.

[0135] The Nz coefficient of the first phase difference layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3. The first phase difference layer may also exhibit a reverse wavelength dispersion characteristic in which the phase difference value increases with the wavelength of the measurement light. In this case, Re(450) / Re(550) of the phase difference layer is preferably greater than 0.8 and less than 1, more preferably greater than 0.8 and less than 0.95.

[0136] The phase difference layer 30 may be formed of any appropriate material as long as it can satisfy the desired characteristics. Specifically, the phase difference layer may be a resin film (stretched film), an alignment solidified layer of a liquid crystal compound, or a combination thereof.

[0137] D-3. Adhesive layer

[0138] The adhesive layer 40 can adopt any appropriate composition. As specific examples, acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives and polyether adhesives can be cited. By adjusting the type, quantity, combination and proportion of the monomers forming the base resin of the adhesive, as well as the amount of the cross-linking agent, the reaction temperature, the reaction time, etc., an adhesive having the desired properties that meet the target can be modulated. The base resin of the adhesive can be used alone or in combination of two or more. The base resin is preferably an acrylic resin (specifically, the adhesive layer is preferably composed of an acrylic adhesive). The thickness of the adhesive layer 40 is, for example, 10μm to 20μm.

[0139] D-4. Preparation of polarizing film

[0140] The polarizing plate can be typically obtained by laminating various layers such as a retardation layer on the polarizing film obtained through the above-mentioned first step and second step.

[0141] Example

[0142] The present invention will be specifically described below by way of examples, but the present invention is not limited to these examples. In addition, the thickness and moisture content of the resin film are values ​​measured using the following measuring methods. In addition, unless otherwise noted, the "parts" and "%" in the examples and comparative examples are weight references.

[0143] 1. Thickness

[0144] The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL Ltd., product name “JSM-7100F”). The thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu Ltd., product name “KC-351C”).

[0145] 2. Moisture content of resin film

[0146] The resin film alone (the resin film after being peeled off from the resin substrate) was dried at 120° C. for 2 hours, and the weight change before and after drying was measured to determine the amount of water contained in the resin film and calculate the water content.

[0147] [Example 1]

[0148] (Production of resin film)

[0149] As the thermoplastic resin substrate, a long amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a water absorption rate of 0.75% and a Tg of about 75° C. was used. One surface of the resin substrate was subjected to a corona treatment.

[0150] To 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z410") in a ratio of 9:1, 13 parts by weight of potassium iodide was added to prepare a PVA aqueous solution (coating solution).

[0151] The PVA aqueous solution was applied onto the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm, thereby producing a laminate.

[0152] The obtained laminate was subjected to free-end single-screw stretching to 2.4 times in the longitudinal direction (longitudinal direction) between rolls of different peripheral speeds in an oven at 130° C. (in-air auxiliary stretching).

[0153] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).

[0154] Next, the film is immersed in a dyeing bath (an iodine aqueous solution obtained by combining iodine and potassium iodide in a weight ratio of 1:7 relative to 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the monomer transmittance (Ts) of the obtained resin film becomes 43% or more (dyeing).

[0155] Next, the film was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).

[0156] Then, while the laminate was immersed in a boric acid aqueous solution (boric acid concentration: 4.0 wt%) at a liquid temperature of 64°C, it was single-screw stretched in the longitudinal direction (length direction) between rolls of different peripheral speeds to a total stretching ratio of 5.5 times (underwater stretching).

[0157] Then, the laminated body was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning).

[0158] Thereafter, the laminate was brought into contact with a SUS heating roll having a surface temperature of 75° C. for about 2 seconds while being dried in an oven maintained at 90° C. (drying). The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment was 5.2%.

[0159] In this manner, a resin film having a thickness of 5.5 μm and a moisture content of 4.4% was formed on the resin substrate.

[0160] Next, a 27 μm thick HC-cycloolefin resin (COP) film was bonded to one side (the side without the resin substrate) of the obtained resin film via an ultraviolet curing adhesive, and then the resin substrate was peeled off from the resin film to obtain a laminate of the HC-COP film and the resin film. The HC-COP film is a film having an HC layer (2 μm thick) formed on the cycloolefin resin (COP) film (25 μm thick), and the film was bonded so that the COP film was on the resin film side.

[0161] The obtained laminate was immersed in a first solution (aqueous solution) having a boric acid concentration of 3% and an iodine concentration of 0.005% at 71° C. for 5 minutes. Thereafter, it was immersed in a water bath (second solution) at room temperature for 15 seconds and dried at 60° C. for 1 minute to obtain a polarizing plate having a HC-COP film and a polarizing film.

[0162] [Example 2]

[0163] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that an aqueous solution having a boric acid concentration of 3% and an iodine concentration of 0.0025% at 70° C. was used as the first liquid and the immersion time in the first liquid was set to 15 minutes.

[0164] [Example 3]

[0165] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that a 70° C. aqueous solution having a boric acid concentration of 4% and an iodine concentration of 0.005% was used as the first liquid and the immersion time in the first liquid was set to 15 minutes.

[0166] [Example 4]

[0167] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that a 70° C. aqueous solution having a boric acid concentration of 4% and an iodine concentration of 0.0025% was used as the first liquid and the immersion time in the first liquid was set to 15 minutes.

[0168] [Example 5]

[0169] A polarizing plate having a HC-COP film and a polarizing membrane was obtained in the same manner as in Example 1 except that an aqueous solution having a boric acid concentration of 5% and an iodine concentration of 0.01% at 81° C. was used as the first liquid and the immersion time in the first liquid was set to 10 minutes.

[0170] [Example 6]

[0171] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that an aqueous solution having a boric acid concentration of 5% and an iodine concentration of 0.005% at 70° C. was used as the first liquid and the immersion time in the first liquid was set to 15 minutes.

[0172] [Example 7]

[0173] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that an aqueous solution having a boric acid concentration of 5% and an iodine concentration of 0.005% at 80° C. was used as the first liquid and the immersion time in the first liquid was set to 10 minutes.

[0174] [Example 8]

[0175] A polarizer having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that an aqueous solution having a boric acid concentration of 5%, an iodine concentration of 0.005% and a temperature of 85°C was used as the first liquid, the immersion time in the first liquid was set to 10 minutes, and an aqueous potassium iodide solution (concentration 1.2%) was used as the second liquid.

[0176] [Example 9]

[0177] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that an aqueous solution having a boric acid concentration of 5%, an iodine concentration of 0.005% and a temperature of 85°C was used as the first liquid, the immersion time in the first liquid was set to 7 minutes, and an aqueous potassium iodide solution (concentration 2.5%) was used as the second liquid.

[0178] [Example 10]

[0179] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that an aqueous solution having a boric acid concentration of 5% and an iodine concentration of 0.0025% at 70° C. was used as the first liquid and the immersion time in the first liquid was set to 15 minutes.

[0180] [Example 11]

[0181] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that a 60° C. aqueous solution having a boric acid concentration of 5% and an iodine concentration of 0.0025% was used as the first liquid and the immersion time in the first liquid was set to 30 minutes.

[0182] [Example 12]

[0183] A polarizer having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that an aqueous solution having a boric acid concentration of 5%, an iodine concentration of 0.0025% and a temperature of 60° C. was used as the first liquid, the immersion time in the first liquid was set to 45 minutes, and an aqueous potassium iodide solution (concentration 2%) was used as the second liquid.

[0184] [Example 13]

[0185] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that an aqueous solution having a boric acid concentration of 8% and an iodine concentration of 0.01% at 80° C. was used as the first liquid and the immersion time in the first liquid was set to 10 minutes.

[0186] [Example 14]

[0187] A polarizer having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that an aqueous solution having a boric acid concentration of 8%, an iodine concentration of 0.01% and a temperature of 90°C was used as the first liquid, the immersion time in the first liquid was set to 10 minutes, and an aqueous potassium iodide solution (concentration 2%) was used as the second liquid.

[0188] [Example 15]

[0189] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that an aqueous solution having a boric acid concentration of 8% and an iodine concentration of 0.003% at 80° C. was used as the first liquid and the immersion time in the first liquid was set to 10 minutes.

[0190] [Example 16]

[0191] The laminate (in a state where a resin film is formed on a resin substrate) is immersed in a first liquid, and an aqueous solution having a boric acid concentration of 4%, an iodine concentration of 0.0025% and a temperature of 70°C is used as the first liquid. The immersion time in the first liquid is set to 5 minutes. Otherwise, a polarizer having a resin substrate and a polarizing film is obtained in the same manner as in Example 1.

[0192] [Example 17]

[0193] The laminate (in a state where a resin film is formed on a resin substrate) is immersed in a first liquid, and an aqueous solution having a boric acid concentration of 4%, an iodine concentration of 0.0025% and a temperature of 70°C is used as the first liquid. The immersion time in the first liquid is set to 10 minutes. Otherwise, a polarizer having a resin substrate and a polarizing film is obtained in the same manner as in Example 1.

[0194] [Comparative Example 1]

[0195] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that the treatment using the first liquid and the second liquid was not performed.

[0196] [Comparative Example 2]

[0197] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that 50° C. water was used as the first liquid, the immersion time in the first liquid was set to 10 minutes, and the treatment with the second liquid was not performed.

[0198] [Comparative Example 3]

[0199] A polarizing plate having a HC-COP film and a polarizing membrane was obtained in the same manner as in Example 1 except that a 5% aqueous solution of boric acid (not containing iodine) at 70° C. was used as the first liquid and the immersion time in the first liquid was set to 5 minutes.

[0200] [Comparative Example 4]

[0201] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Example 1 except that a 50° C. aqueous solution having a boric acid concentration of 4% and an iodine concentration of 0.003% was used as the first liquid and the immersion time in the first liquid was set to 30 minutes.

[0202] [Comparative Example 5]

[0203] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Comparative Example 1 except that the dyeing conditions were adjusted.

[0204] [Reference Example 1]

[0205] (Production of resin film)

[0206] A long roll of a 30 μm thick PVA resin film (manufactured by Kuraray, trade name "PE3000") was stretched in the longitudinal direction by a single screw at 66°C using a roller stretching machine to give a total stretching ratio of 6.5 times, and was simultaneously subjected to swelling, dyeing, cross-linking and cleaning treatments, and finally dried to produce a resin film with a thickness of 12 μm and a moisture content of 11%.

[0207] The swelling treatment was carried out in pure water at 20°C while stretching. Next, the dyeing treatment was carried out in an aqueous solution at 30°C with a weight ratio of iodine to potassium iodide of 1:7 while stretching, and the iodine concentration of the aqueous solution was adjusted so that the monomer transmittance of the obtained resin film was 42% or more. Next, the crosslinking treatment was a two-stage crosslinking treatment, and the first stage of the crosslinking treatment was carried out in an aqueous solution at 40°C in which boric acid and potassium iodide were dissolved while stretching. The boric acid content of the aqueous solution in the first stage of the crosslinking treatment was 5.0% by weight, and the potassium iodide content was 3.0% by weight. The second stage of the crosslinking treatment was carried out in an aqueous solution at 65°C in which boric acid and potassium iodide were dissolved while stretching. The boric acid content of the aqueous solution in the second stage of the crosslinking treatment was 4.3% by weight, and the potassium iodide content was 5.0% by weight. Next, the washing treatment was carried out with a potassium iodide aqueous solution at 20°C. The potassium iodide content of the washing treatment aqueous solution was set to 2.6% by weight. Finally, a drying treatment was carried out at 70°C for 5 minutes to obtain a resin film.

[0208] A 27 μm-thick HC-COP film was bonded to one surface of the obtained resin film via an ultraviolet curing adhesive to obtain a laminate (polarizing plate) of the HC-COP film and the resin film.

[0209] [Reference Example 2]

[0210] The laminate of Reference Example 1 was immersed in a first solution (aqueous solution) having a boric acid concentration of 6% and an iodine concentration of 0.003% at 80° C. for 20 minutes. Thereafter, it was immersed in a water bath (second solution) at room temperature for 15 seconds and then dried at 60° C. for 1 minute to obtain a polarizing plate having a HC-COP film and a polarizing film.

[0211] [Reference Example 3]

[0212] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Reference Example 2 except that the temperature of the first liquid was 75° C. and the immersion time in the first liquid was 30 minutes.

[0213] [Reference Example 4]

[0214] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Reference Example 2 except that the boric acid concentration of the first solution was 8% and the immersion time in the first solution was 30 minutes.

[0215] [Reference Example 5]

[0216] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Reference Example 1 except that the dyeing conditions were adjusted.

[0217] The following evaluations were performed on the Examples, Comparative Examples, and Reference Examples. The evaluation results are summarized in Table 1. Figure 4 , a representative diagram of the evaluation of the following appearance 1 (the evaluation results of Comparative Example 5, Example 9 and Example 8) is shown. Figure 5 2 shows a representative diagram of the evaluation of the appearance 2 described below (the evaluation results of Comparative Example 5, Example 9, and Example 8).

[0218] <Evaluation>

[0219] Single unit transmittance and polarization degree

[0220] For the polarizing film (polarizing film / HC-COP film), a UV-visible spectrophotometer (manufactured by JASCO Corporation, V-7100) was used for measurement, and the measured single transmittance Ts, parallel transmittance Tp, and orthogonal transmittance Tc were respectively used as Ts, Tp, and Tc of the polarizing film. These Ts, Tp, and Tc are measured with a 2-degree field of view (C light source) of JIS Z8701 and the Y value after visibility correction.

[0221] The polarization degree P is calculated from the obtained Tp and Tc using the following formula.

[0222] Polarization degree P (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0223] Hue (a and b)

[0224] The single-body hue of the polarizing film (polarizing film / HC-COP film) was measured using an ultraviolet-visible spectrophotometer (V-7100, manufactured by JASCO Corporation).

[0225] Appearance 1

[0226] The obtained polarizer was used to prepare a laminate for evaluation. Specifically, after the following phase difference layer was attached to the polarizing film side of the polarizer via an acrylic adhesive layer (15 μm), a reflector (TORAY ADVANCED FILM Co., Ltd., "Cerapeel DMS-X42") was attached to the phase difference layer via an acrylic adhesive layer (15 μm) to obtain a laminate for evaluation. In addition, the reflectivity measured by the spectrophotometer (Konica Minolta, "CM-2600d") of the reflector in SCI mode was 88%.

[0227] The appearance (presence or absence of streaks) of the obtained laminate for evaluation was visually observed when viewed from the polarizing plate side.

[0228] (Evaluation Criteria)

[0229] Good: No streaks detected

[0230] Bad: Streaks were detected

[0231] (Preparation of stretched film constituting phase difference layer)

[0232] The polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and a reflux cooler controlled at 100° C. 29.60 parts by mass (0.046 mol) of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane, 29.21 parts by mass (0.200 mol) of isosorbide (ISB), 42.28 parts by mass (0.139 mol) of spiroglycerol (SPG), 63.77 parts by mass (0.298 mol) of diphenyl carbonate (DPC) and 1.19×10 calcium acetate monohydrate as a catalyst were added. -2 Mass parts (6.78×10 -5 mol). After the reactor was decompressed and replaced with nitrogen, it was heated with a heat medium and stirring was started when the internal temperature reached 100°C. After 40 minutes from the start of heating, the internal temperature reached 220°C, and the pressure was reduced while being controlled to maintain the temperature. After reaching 220°C, it was reduced to 13.3 kPa in 90 minutes. The phenol vapor generated as a by-product accompanying the polymerization reaction was introduced into a 100°C reflux cooler, and a certain amount of monomer components contained in the phenol vapor was returned to the reactor, and the uncondensed phenol vapor was introduced into a 45°C condenser for recovery. Nitrogen was introduced into the first reactor to temporarily return it to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, heating and decompression in the second reactor were started, and the internal temperature was made to 240°C and the pressure was made to 0.2 kPa in 50 minutes. Then, polymerization was carried out until the specified stirring power was reached. When the specified power was reached, nitrogen was introduced into the reactor to restore the pressure, and the generated polyester carbonate resin was extruded into water, and the bundle was cut to obtain pellets.

[0233] The obtained polyester carbonate resin (pellets) was vacuum dried at 80°C for 5 hours, and then a film-making device equipped with a single screw extruder (manufactured by Toshiba Machine Co., Ltd., barrel setting temperature: 250°C), a T-die (width 200mm, setting temperature: 250°C), a cooling roller (setting temperature: 120-130°C) and a winder was used to produce a long strip of resin film with a thickness of 135μm. The obtained long strip of resin film was stretched in the width direction at a stretching temperature of 143°C and a stretching ratio of 2.8 times to obtain a stretched film with a thickness of 47μm. The Re(550) of the obtained stretched film was 143nm, Re(450) / Re(550) was 0.86, and the Nz coefficient was 1.12.

[0234] A film exhibiting the refractive index property of nz>nx=ny (manufactured by Dai Nippon Printing Co., Ltd., "MCP-N(100)", Rth(550): -135nm) is bonded to the above-obtained stretched film via an ultraviolet curing adhesive (thickness after curing: 1.0μm) to obtain a laminated film constituting a phase difference layer.

[0235] Appearance 2

[0236] While the LED backlight (Altek, 7200 cd measured by TOPCON TECHNOHOUSE "SR-UL1R" at a measuring angle of 1.0 deg and a height of 50 cm) was on, the first polarizer (Nitto, "SEG1224DUHC", transmittance 43%), the obtained polarizer, and the second polarizer (Nitto, "SEG1224DUHC", transmittance 43%) were sequentially arranged thereon, and the appearance (presence or absence of stripes) when viewed from the second polarizer was visually observed. The three polarizers were arranged in such a way that the absorption axes of the adjacent polarizers were orthogonal (three-piece cross method). In addition, the first polarizer and the second polarizer were arranged in a state of being bonded to a glass plate.

[0237] (Evaluation Criteria)

[0238] Good: No streaks detected

[0239] Defective: Stripe Table 1 confirmed

[0240]

[0241] In the comparative example, streaks were visually recognized along the absorption axis direction (stretching direction) of the polarizing film, but no streaks were visually recognized in the examples. In addition, it is believed that in the comparative example 2 using the first liquid without boric acid, iodine would fall off from the weakly cross-linked portion, and streaks would be more visually recognized.

[0242] Industrial Applicability

[0243] The polarizing film according to the embodiment of the present invention can be suitably used in image display devices such as liquid crystal display devices, organic EL display devices, and inorganic EL display devices.

[0244] Explanation of symbols

[0245] 1Layer

[0246] 2Thermoplastic resin substrate

[0247] 3. Polyvinyl alcohol (PVA) resin layer

[0248] 10 Polarizing film

[0249] 20 protective layer

[0250] 30 Phase difference layer

[0251] 40 Adhesive layer

[0252] 100 polarizers

Claims

1. A method for manufacturing a polarizing film, comprising the steps of: bringing a resin film containing iodine and having a water content of 15 wt % or less into contact with a first liquid; The first liquid is an aqueous solution of boric acid and iodine, and the temperature of the first liquid is 60° C. or higher.

2. The manufacturing method according to claim 1, wherein: The resin film in contact with the first liquid has a single body transmittance of 44% or more.

3. The manufacturing method according to claim 1 or 2, wherein: The boric acid concentration of the first liquid is 3% by weight or more.

4. The manufacturing method according to any one of claims 1 to 3, wherein: The iodine concentration of the first liquid is 0.002 wt % to 0.01 wt %. 5 . The production method according to claim 1 , comprising the step of bringing the resin film in contact with the first liquid into contact with a second liquid.

6. The manufacturing method according to claim 5, wherein: The second liquid includes water. 7 . The production method according to claim 1 , wherein a polarizing film having a thickness of 22 μm or less is obtained.